VD_FINDINFO Décision / 2012 / 171 vom 5. Dezember 2011 - VD Tribunal cantonal (2011)
DÉCISION D'IRRECEVABILITÉ, NON-LIEU, PROPAGATION D'UNE MALADIE DE L'HOMME | 231 CP, 310 CPP (CH), 393 al. 1 let. a CPP (CH)